5 year review of gastroschisis diagnoses and outcomes in a district general hospital (DGH). (18th April 2012) - Finney, V; Brigham, S; Wetherill, C
Abstract : Introduction: Gastroschisis affects 2.8-4.4 per 100, 000 births in England and Wales having a 98% detection rate by ultrasound 18 – 20+6 weeks. The aim of our review was to ensure that our detection rates were in accordance with the national standards, to look at the outcomes for the babies affected, ensuring they receive optimum care in a DGH Patients and methods: This was a retrospective audit of patients diagnosed with gastroschisis 2005-2010. Antenatal management plans, referral to the paediatricians, surgeons and neonatal outcomes were viewed. Results: 100% patients were diagnosed antenatally by 20+6 weeks. One patient had a TOP for unplanned pregnancy. One patient transferred care to the tertiary centre. All of the remaining patients were followed up in the fetal medicine unit in the DGH and 82% had paediatric review prior to delivery. Two were transferred out for delivery due to lack of neonatal cots. Following delivery all were transferred to the surgical unit, undergoing surgery. One baby delivered at 29/40 died at 3 days due to complications of prematurity. The remainder had either no or minor complications with the majority with no long term problems anticipated. Conclusion: 11 patients were diagnosed antenatally in accordance with the national fetal anomaly screening standards. Patients received consistent care and none required referral for tertiary service care. Only small numbers of babies affected by gastroschisis are diagnosed annually in a DGH, however they can be managed appropriately with good outcomes.